BUY NOW PAY LATER: EMERGING TECHNIQUE IN ONLINE SHOPPING FOR ATTRACTING CONSUMERS - Singh, Namrata; Sahni, Sangeeta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The "Buy Now, Pay Later" (BNPL) model has emerged as a transformative technique in online shopping, reshaping consumer purchasing behavior. BNPL allows consumers to make purchases instantly while deferring payments through interest-free installments, thereby enhancing affordability and convenience. This study explores the growing adoption of BNPL services, analyzing their impact on consumer attraction, purchasing decisions, and financial behavior. The research examines key drivers behind BNPL adoption, including ease of access, minimal credit checks, and flexible repayment options. Additionally, it investigates potential challenges such as debt accumulation, regulatory concerns, and financial literacy gaps. The Findings indicate that BNPL significantly influences impulse buying, particularly among younger demographics and online shoppers seeking budget-friendly alternatives to credit cards. However, concerns regarding overspending and long-term financial consequences highlight the need for consumer awareness and responsible usage. Although the data shows gender-based differences in digital payments, financial inclusion, and e-commerce, none of these differences are statistically significant (all Sig. > 0.05). This means that while trends exist, gender alone does not play a decisive role in shaping these behaviors in online shopping within this dataset. Further research with a larger sample size may provide deeper insights into these trends.